ANALISIS ZAKAT SEBAGAI PENDAPATAN ASLI DAERAH TERHADAP INDEKS PEMBANGUNAN MANUSIA: PENDEKATAN DATA PANEL (Studi Kasus 12 Kabupaten/Kota Provinsi Aceh) - Cut Risya Varlitya (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2017)
This study aims to analyze the effect of zakat as Regional Own Source Revenue (PAD) on Human Development Index (HDI) in 12 districts in Aceh Province. The study used panel data from 2014 to 2016, with Simple Linear Regression analysis. The results showed that each increase in zakat income as a source of PAD by 1 percent will also increase the human development index (HDI) by 1,14. percent, assuming that other variables are constant. Therefore, we concludes that zakat as a source of PAD gives a positive influence for the improvement of human development index (HDI) in 12 districtsin Aceh Province.Moreover, it is suggested to Baitul Mal as the institution of zakat distribution to increase the socialization of the benefit of zakat as the income of the region and improve the role of local government, local communities to monitor and ensure that zakat is given to communities according to the criteria of the recipient of zakat.